ABOUT DATING OF PETROGLYPHS OF GOBUSTAN (AZERBAIJAN) - Faradzeva, Malahat Novruz (History, Archeology and Ethnography of the Caucasus, 2021)
Since the discovery of the petroglyphs of Gobustan, there have been numerous studies of petroglyphs, field work on documentation, and archeological excavations. Despite the extensive literature on Gobustan, the issue of dating the rock paintings remains controversial. The author of the paper, using the results of radiocarbon dating and the 3D Studio Max software, classifies the petroglyphs by periods. As a result, the oldest date – 13 610 CD (calibrated date) – was revealed in Gobustan in the rocky shelter of Gaya Arasi on the Kichikdash mountain. The next oldest date is approximately 10,600 CD, which was obtained from the cultural layer of the Ana-zaga cave of the Beyukdash mountain. Considering that the Late Khvalyn transgression took place nearly 14,000 years ago, and during this period the waters of the Khvalyn Sea washed the Beyukdash, Kichikdash and Dzhingirdag mountains, the interval between these dates may be due to the fluctuations of the sea level. Based on the research carried out and the dates obtained, the author singles out 9 stylistic and chronological trends in the petroglyphs of Gobustan, including the period of the Middle Ages and the Modern Age. The author emphasizes that the uniqueness of the Gobustan archaeological complex lies in the fact that separate stones with petroglyphs identical to the rock carvings on the walls of the caves were discovered from dated cultural layers. In addition, stylistic and comparative analysis allowed the author to date the rock carvings of Gobustan.As a result of the research, it has been revealed that the settlements of the end of the Upper Paleolithic and Mesolithic Ages were mainly located on the upper terraces of the mountains. In the Neolithic and Eneolithic Ages, with the rise in the level of the Caspian Sea, the caves retained the status of the main place of residence. With the lowering of the sea level in the Bronze Age, the middle and lower terraces were inhabited. During this period, the settlers of Gobustan, who were engaged in cattle breeding, painted images of bezoar goats with large curved horns on the rocks. At the foot of the mountains, the round settlements and the tradition of kurgan burials emerged.
Keywords: petroglyphs of Gobustan; Ana-zaga cave; Gaya Arasi; Firuz; Beyukdash; Kichikdash; dating of petroglyphs; Gobustan archeological complex